Pemanfaatan Media Sosial Sebagai Media Promosi Pariwisata Kabupaten Trenggalek Untuk Gen Z Di Jawa Timur - Rizqi Anggita, Esa Shafatta; Abdin Munib, Jazuli (Besaung : Jurnal Seni Desain dan Budaya, 2025)
The tourism sector has proven to be reliable in improving people's welfare and national development. Trenggalek Regency as one of the areas in East Java Province that has quite a lot of tourism potential with very promising future prospects. Gen Z can be one of the spearheads of tourism ambassadors in each region. Gen-Z will spend more time playing the internet, especially social media because social media has become one of the most effective communication tools to promote various things, including the tourism potential of an area of ​​Trenggalek Regency. Using a qualitative approach and Design Thinking method, this study went through five stages: empathize, define, ideate, prototype, and test. This method is used to observe problems in tourism promotion, create visual works based on existing data sources, and design solutions to existing problems. The use of social media as a promotional medium is carried out through Instagram. The main media published through Instagram is very effective in increasing reach out and awareness of 12 tourist destinations in Trenggalek Regency, and the use of content pillars has an effect on social media engagement. In addition, supporting media used such as travel books are also useful for all groups, the use of logos in each post can increase the recognition of the @trenggalek.tourism Instagram account